Cluster Analysis and Principal Component Analysis using Micropollutant Measurements on the Most Polluted Tributary of Ergene River: Çorlu Stream - Cingiroglu, Fulya; Emadian, SeyedMehdi; Tezel, Ulas; Kaynak, Burcak (Cosmos S.A., 2022)
This study focuses on investigation the spatial distribution of pollutants in Çorlu Stream is the highest industrialized tributary of Ergene River which is one of the most polluted rivers in Turkey. A total of 250 conventional, metal and micropollutants were scanned at eleven sampling locations for four seasons in Çorlu Stream of Ergene River. At these locations, total of 126, 124, 99 and 107 pollutants were detected at least one sampling location in summer, fall, winter and spring, respectively. Four micropollutants which are associated with textile industry were detected in every location in all seasons. Cluster Analysis found four main clusters for sampling locations from most polluted to low polluted, and six cluster for pollutants ranging from conventional to unique pollutants. Principal Component Analysis identified six components for every season explaining more than 80% of the variation in each. PCA results indicated the impact of textile, leather, metal industries and appliance-electronics production in the Çorlu Region.